Musical Practices in Early Melodic Death Metal (Journal of Music Research Online, 2022)
This article investigates early examples of melodic death metal, a subgenre of metal that developed mainly in Gothenburg, Sweden, in the early- to mid-1990s. I examine how harmony is used in melodic death metal by undertaking a musical analysis of excerpts from three albums: The Gallery by Dark Tranquillity (1995), Slaughter of the Soul by At The Gates (1995), and The Jester Race by In Flames (1996). These analyses reveal a transformation of harmonic practices from melodic death metal’s parent genres of New Wave of European Heavy Metal and Swedish death metal. Melodic death metal also develops its own unique harmonic practices that point to a need to consider this style as a discrete subgenre beyond its development as The Gothenburg Sound. This enables a discussion of how these practices defined melodic death metal during its formative years and develops an argument for the differentiation of melodic death metal from local death metal sounds on musicological grounds. This article complements existing studies of melodic death metal by investigating an earlier period in the genre’s development than previous studies have observed and provides a foundation for further investigation into the development and proliferation of extreme metal subgenres.